2015
DOI: 10.1002/lary.25682
|View full text |Cite
|
Sign up to set email alerts
|

Age: An effect modifier of the association between allergic rhinitis and Otitis media with effusion

Abstract: 2c. Laryngoscope, 126:1687-1692, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…A large body of work suggests a link between atopic disease and OM, and particularly COME. These associated atopic diseases include allergic rhinitis (Alles et al, 2001; Kreiner-Moller et al, 2012; Roditi et al, 2016), eczema (MacIntyre et al, 2010), and asthma (Gamble et al, 1992; Eldeirawi et al, 2010; MacIntyre et al, 2010; Bjur et al, 2012), but the same associations are not always reproduced between studies, leading to significant debate about the nature of these associations (Zernotti et al, 2017). Gamble et al (1992) hypothesized that COME in asthmatics is not an isolated disease, but instead represents an atopic disease affecting the mucociliary system of entire respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of work suggests a link between atopic disease and OM, and particularly COME. These associated atopic diseases include allergic rhinitis (Alles et al, 2001; Kreiner-Moller et al, 2012; Roditi et al, 2016), eczema (MacIntyre et al, 2010), and asthma (Gamble et al, 1992; Eldeirawi et al, 2010; MacIntyre et al, 2010; Bjur et al, 2012), but the same associations are not always reproduced between studies, leading to significant debate about the nature of these associations (Zernotti et al, 2017). Gamble et al (1992) hypothesized that COME in asthmatics is not an isolated disease, but instead represents an atopic disease affecting the mucociliary system of entire respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 However there is one study from Harvard medical school, which says the presence of AR increases the odds of otitis media with effusion, Eustachian tube dysfunction and tympanic membrane retraction in children more than 6 yrs old. 9 No further reference could be found in the literature where tympanic membrane retraction is studied in correlation with allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Though allergic rhinitis is accepted as one of the leading causes of ET dysfunction and OME in many studies none of these studies include TM retraction as feature associated with AR. [3][4][5][6]9 Since Eustachian tube dysfunction will lead to negative middle ear pressure, TM retraction can develop in these patients. The reason for not seeing a statistically significant correlation between duration of symptoms and TM retraction may be due to the fact that these patients may have compromised ET function and thus retraction of TM only during exacerbation of symptoms and not as a persistent feature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that age, gender, race, genetic factors, low socioeconomic status, breastfeeding, allergic diseases, and chronic sinusitis were associated with otitis media 6,7,15,16 . Several studies of them reported that allergic rhinitis was a risk factor affecting the occurrence of otitis media 17 .…”
Section: Introductionmentioning
confidence: 99%